2021
DOI: 10.1158/1078-0432.ccr-21-0701
|View full text |Cite
|
Sign up to set email alerts
|

TP53 Mutations with Low Variant Allele Frequency Predict Short Survival in Chronic Lymphocytic Leukemia

Abstract: Purpose: In chronic lymphocytic leukemia (CLL), TP53 mutations are associated with reduced survival and resistance to standard chemoimmunotherapy (CIT). Nevertheless, the clinical impact of subclonal TP53 mutations below 10% to 15% variant allele frequency (VAF) remains unclear. Experimental Design: Using a training/validation approach, we retrospectively analyzed the clinical and biological features of TP53 mutations above (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(73 citation statements)
references
References 53 publications
5
55
1
Order By: Relevance
“…The clinical consequence of TP53 mutations was similar when patients with low VAF were stratified into subclasses <1%, between 1% and 5% or 5% and 10%. Shorter OS was also confirmed when separately considering patients with single or multiple mutations classified as high VAF or low VAF ( 15 , 20 ).…”
Section: Low- and High-burden Tp53 Mutations Have ...mentioning
confidence: 69%
See 4 more Smart Citations
“…The clinical consequence of TP53 mutations was similar when patients with low VAF were stratified into subclasses <1%, between 1% and 5% or 5% and 10%. Shorter OS was also confirmed when separately considering patients with single or multiple mutations classified as high VAF or low VAF ( 15 , 20 ).…”
Section: Low- and High-burden Tp53 Mutations Have ...mentioning
confidence: 69%
“…Focusing on studies designed to assess overall survival (OS) between cases harboring the wild-type TP53 gene versus cases with low-burden TP53 variant (15,18,20,35), the frequencies of TP53 mutation ranged from 10.6 to 27.5%, of which 26.8 to 45.2% cases exclusively harbored low-burden TP53 mutations depending on the threshold used to discriminate between lowand high-VAF TP53 mutations. Blakemore et al failed to demonstrate a clinical impact of low-burden TP53 mutations but identified an intermediate-risk group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations